2021
DOI: 10.1111/polp.12389
|View full text |Cite
|
Sign up to set email alerts
|

Cocked, Locked, and Loaded: An Analysis of the Five Policy Regimes of Concealed Carry on College Campuses

Abstract: What are the predictors of the five types of policy regimes on campus carry across the 50 U.S. states? This study explores the roles of problem environment, gun culture, state policy liberalism, region, and racial politics to answer that research question. We argue that morality policy, the role of region in the adoption of public policy, and the southern subculture of violence are useful theoretical lenses for examining campus carry. We find that the problem environment-measured as gun murders per 100,000 pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, LaPlant and others (2021) examined the factors that can predict whether states adopted campus carry policies or not. They found that state liberalism, the extent of the gun culture in a given state, and number of minorities in the state, all had an impact.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, LaPlant and others (2021) examined the factors that can predict whether states adopted campus carry policies or not. They found that state liberalism, the extent of the gun culture in a given state, and number of minorities in the state, all had an impact.…”
Section: Resultsmentioning
confidence: 99%
“…LaPlant et al. (2021) explore the five types of policy regimes on campus carry laws across the 50 states from strict prohibition by law to concealed carry on college campuses being fully allowed by law. The analysis reveals that an interaction term of the South and the percentage minority population (percentage African American + percentage Hispanic) is a strong predictor of the adoption of campus carry laws.…”
Section: Gun Policymentioning
confidence: 99%